Apple pectin-derived oligosaccharides produce carbon dioxide radical anion in Fenton reaction and prevent growth of Escherichia coli and Staphylococcus aureus. (October 2017) - Martinov, Jelena; Krstić, Miodrag; Spasić, Snežana; Miletić, Srdjan; Stefanović-Kojić, Jovana; Nikolić-Kokić, Aleksandra; Blagojević, Duško; Spasojević, Ivan; Spasić, Mihajlo B.
Abstract: Pectin is the main soluble fiber in apples or citruses. It may be fermented by gut microbiota to metabolites showing local intestinal and systemic effects. A wide range of beneficial effects of dietary pectin includes impacts on the redox milieu and microbiota profile. We prepared pectin-derived oligosaccharides (apple (APDO) and citrus) and polygalacturonic acid-derived oligosaccharides, using alkaline hydrolysis by hydrogen peroxide, and analyzed them by Fourier Transform Infrared spectrometry. Furthermore, we analyzed the effects of pectin-derived oligosaccharides on hydroxyl radical (HO)-generating Fenton reaction using electron paramagnetic resonance spin-trapping spectroscopy, and the effects on the growth of Escherichia coli and Staphylococcus aureus in the presence of dietary-relevant HO-generating system (iron + ascorbate). The oligosaccharides react with HO radical to produce carbon dioxide radical anion (CO2 − ). A comparative analysis showed that APDO has the most prominent bacteriostatic effect. This might be at least partially related to the higher capacity of APDO to produce CO2 −, which specifically targets proteins and appears to have a longer lifetime and larger diffusion radius in biological systems compared to HO. Graphical abstract: Highlights: Pectine derived oligosaccharides react with HO radical to produce CO2 − . Apple pectin derived oligosaccharides has the most bacteriostatic effect. Bacteriostatic effect is related with oligosaccharides ability to produce CO2 .